2007
DOI: 10.1088/1126-6708/2007/01/090
|View full text |Cite
|
Sign up to set email alerts
|

AdS bubbles, entropy and closed string tachyons

Abstract: We study the conjectured connection between AdS bubbles (AdS solitons) and closed string tachyon condensations. We confirm that the entanglement entropy, which measures the degree of freedom, decreases under the tachyon condensation. The entropies in supergravity and free Yang-Mills agree with each other remarkably. Next we consider the tachyon condensation on the AdS twisted circle and argue that its endpoint is given by the twisted AdS bubble, defined by the double Wick rotation of rotating black 3-brane sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
310
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(334 citation statements)
references
References 79 publications
24
310
0
Order By: Relevance
“…6) we conclude that the holographic type A Weyl anomaly in d = 2n dimensions is a n E 2n with a n as in (A.1).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…6) we conclude that the holographic type A Weyl anomaly in d = 2n dimensions is a n E 2n with a n as in (A.1).…”
Section: Discussionmentioning
confidence: 56%
“…There it was observed that while the type B Weyl anomalies have a trivial descent, the unique (in any even dimensions) type A anomaly has a non-trivial descent. 6 These features might, in fact, serve as the defining distinction between the two classes of anomalies, which can also be applied to the hypersurface anomalies discussed in Section 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entanglement entropy is considered as an effective measure of how a given quantum system is strongly correlated. It has been proven as a powerful tool to describe different phases and the corresponding phase transitions in holographic superconductors [86]- [98]. In this section, we will calculate the holographic entangle entropy in the non-equilibrium process and further disclose that the entanglement entropy can be regarded as a useful tool in describing the holographic superconductor.…”
Section: Holographic Entanglement Entropymentioning
confidence: 97%
“…The entanglement entropy is directly related to the degrees of freedom of a system to keep track of them. From [86,99,100], we can see in a time-dependent background the entanglement entropy associated with a specified region on the boundary in the context of the AdS/CFT correspondence is given by the area of a co-dimension two bulk surface with vanishing expansions of null geodesics. We will follow this treatment to calculate the entanglement entropy in the time-dependent background.…”
Section: Holographic Entanglement Entropymentioning
confidence: 99%